Professional Insights Provided by Women Extension Personnel in Odisha - Saha, Parnika; Prusty, Ajay Kumar; Nanda, Chinmaya; Ray, Soumik; Sahoo, wajit (Indian Journal of Extension Education, 2024)
The extension services offered by the extension professionals to the agricultural community are more diversified now than ever and will continue to vary to satisfy the growing demand. The effectiveness and productivity of the services are highly influenced by the performance of the extension professionals involved. To study their level of professionalism, it is imperative to know the factors that hinder their professionalism level. This study was conducted in the year 2023-2024 in Odisha to assess contributory factors affecting professionalism and seek suggestions to overcome those problems. A sample comprising 120 women agricultural extension personnel was selected through purposive sampling. The rank-based quotient (RBQ) method was applied to analyse the constraints perceived by respondents, and the word cloud tool was used to analyse the suggestions received using the R software. The significant barriers that restricted the women extension functionaries from exerting their professionalism level were receiving less training, mobility challenges, and an insufficient workforce. Further, to overcome the challenges, women agricultural extension personnel suggested the provision of skill based workshops related to advanced technology use and efficient allocation of operational resources could enhance their performance level.
Keywords: Constraints; Professionalism; Rank based quotient; Suggestions; Women extension personnel